Investigating the In Vivo Effects of Anti-Prion Protein Nanobodies on Prion Disease with AAV Vector - Jingjing Zhang; Mengfei Wang; Dan Wang; Xiangyi Zhang; Yue Ma; Els Pardon; Jan Steyaert; Romany Abskharon; Fei Wang; Jiyan Ma (Pathogens)
Prion diseases are fatal neurodegenerative disorders affecting humans and animals, and the central pathogenic event is the conversion of normal prion protein (PrPC) into the pathogenic PrPSc isoform. Previous studies have identified nanobodies that specifically recognize PrPC and inhibit the PrPC to PrPSc conversion in vitro. In this study, we investigated the potential for in vivo expression of anti-PrPC nanobodies and evaluated their impact on prion disease. The coding sequences of three nanobodies were packaged into recombinant adeno-associated virus (rAAV) and were administered via intracerebroventricular (ICV) injection in newborn mice. We found that the expression of these nanobodies remained robust for over 180 days, with no observed detrimental effects. To assess their therapeutic potential, we performed ICV injections of nanobody-expressing rAAVs in newborn mice, followed by intracerebral prion inoculation at 5–6 weeks of age. One nanobody exhibited a small yet statistically significant therapeutic effect, extending survival time from 176 days to 184 days. Analyses of diseased brains revealed that the nanobodies did not alter the pathological changes. Our findings suggest that high levels of anti-PrPC nanobodies are necessary to delay disease progression. Further optimization of the nanobodies, AAV vectors, or delivery methods is essential to achieve a significant therapeutic effect.